Perancangan Sistem Pembacaan Data Kwh Meter Prabayar Merk Itron Em512 Type 700 Java Dengan Vb.Net 2010 - Elkin Rilvani (Jurnal SIGMA, 2021)
Along with the development of information technology utilization also applied in the field of electricity kwh meter by supporting smart electricity program (Prepaid). KWh Meter Prepaid brand Itron EM512 Java Type 700 is a prepaid meter that has kwaliatas best to display the number of calculations in HyperTerminal combined with VB.Net 2010 and Sql Server 2008 aims to do kwh meter reading data at a more granular and detailed with Burst Data Output (DBO). In the journal we will discuss system design data reading prepaid brands kwh meter ITRON type em512 700 java With vb.net 2010. Keywords : KWh Meter Prepaid, HyperTerminal, Burst Data Output, VB.net 2010